PENGARUH GRADING DAN LYMPHOVASCULAR INVASION TERHADAP METASTASIS KELENJAR GETAH BENING AXILLA PADA KANKER PAYUDARA - Albert Simon; Tjakra Wibawa Manuaba (E-Jurnal Medika Udayana, 2016)
In Indonesia, breast cancer is the 2nd highest type of cancer. This study was conducted to know the correlation between breast cancer grading and lymphovascular invasion (LVI) with axillary lymph node metastases. This study was carried out by; 1) obtaining the sample from medical record and pathology anatomy examination report of breast cancer patient from RSUP Sanglah 2013, 2) examining the correlation between grading with axillary lymph node metastases and correlation between LVI with axillary lymph node metastases using chisquare, 3) Examining the strength of correlation between grading with axillary lymph node metastases and LVI with axillary lymph node metastases using RO. This study consists of 51 samples which diagnosed with advance breast cancer. The result of this study shows; 1) no correlation between grading with axillary lymph node metastases, 2) there is correlation between LVI with axillary lymph node metastases, 3) the strength of correlation between LVI with axillary lymph node metastases are RO=5.34 with the percentage of 84%.    In conclusion, LVI is correlated with axillary lymph node metastases. Further study about other factors which effecting the axillary lymph node metastases and the correlation of grading and LVI with axillary lymph node metastases in early breast cancer should be conducted in order to give more clear information.